Transcranial Alternating Current Stimulation With Gamma Oscillations Over the Primary Motor Cortex and Cerebellar Hemisphere Improved Visuomotor Performance - Miyaguchi, Shota; Otsuru, Naofumi; Kojima, Sho; Saito, Kei; Inukai, Yasuto; Masaki, Mitsuhiro; Onishi, Hideaki (Frontiers in Behavioral Neuroscience, 2018)
Transcranial alternating current stimulation (tACS) can be used to modulate oscillatory brain activity. In this study, we investigated whether tACS applied over the primary motor cortex (M1) and cerebellar cortex region improved motor performance. We applied tACS (1.0 mA) to 20 healthy adults while they performed an isometric force task with some visuomotor control using their right index finger. Gamma (70 Hz) oscillations in the Experiment 1 or beta (20 Hz) oscillations in the Experiment 2 were applied for 30 s over the left M1, right cerebellar hemisphere or both regions (“M1-Cerebellum”), and errors performing the task were compared. Beta-oscillation tACS did not affect motor performance. With the gamma-oscillation tACS, a negative correlation was found between the difference of error in the M1-Cerebellum condition and the number of errors in the sham condition (P = 0.005, Pearson’s r = −0.597), indicating that motor performance improved with M1-Cerebellum tACS for subjects with low motor performance in the sham condition. Those who performed poorly in the sham condition made significantly fewer errors with M1-Cerebellum tACS (P = 0.004). Thus, for subjects with poorer motor performance, tACS with gamma oscillations applied over the M1 and contralateral cerebellar hemisphere improved their performance.